Information Real-Time Delivery (IRTD) System through the Internet of Things (IoT): An Improvement in Truck Management Environment - B, Adnan H. .; K, Rahimah .; M, Hasnah .; Zakaria, Izatul Husna (International Journal of Engineering and Technology, 2018)
Today, logistics sector, particularly in container haulage industry, is dealing with million shipments of cargo every day, origin and destination, size, weight, content, and location are all tracked across the global delivery network. in and out containers at the port can cause the port congestion and additionally are going to affect driver to deliver the cargo to the customer at the right time. Due to that matter, container haulage invariably received lots of complaint by the customer concerning the delay of the cargo without customer grasp precisely situation that faced by a driver in order to deliver the customer’s goods. The delay of this cargo may occur as a result of waiting time at the port terminal, customs clearance, road congestion, bad weather, and the breakdown of truck and shortage of driver. All this information is late received by the customer and it will affect the level of customer satisfaction. This study proposed to conduct a research about the Information Real-Time Delivery Systems IRTD through the Internet of Things (IoT) that can give the information of real-time monitoring and updated delivery systems to related parties. Thus, these papers focuses on the current process of the information notification delivery model to the related parties and resolve the uncertainties delays by redesign model of information real-time delivery system at haulage industry. Furthermore, this research will determine the utilization benefit of IRTD system at haulage industry. Business Process Redesign model will be adopted in this study as a holistic guidance about a development model of IRTD integrated IoT technology as an improvement in haulage industry environment.